Process thermoneutral point in dry autothermal reforming for CO2 utilization. (March 2017) - Kale, Ganesh R.; Doke, Suhas; Anjikar, Ajinkya
Graphical abstract: Highlights: Dry autothermal reforming is a novel CO2 utilization process. Process thermoneutral points were determined in this theoretical study. The process thermoneutral points are better than reactor thermoneutral points. This study can be used to operate the process without external thermal energy. This study can be used for any autothermal process. Abstract: Dry autothermal reforming is a novel CO2 utilization process. Thermoneutral points are considered to be the best operating points in autothermal reforming reactors. A theoretical study was done to determine the process thermoneutral points for complete dry autothermal reforming process considering the basic preheater, reactor and condenser configuration. The results were compared to the product yields at reactor thermoneutral points for the same input feed and temperature conditions. The process thermoneutral points were found be better for operational reasons than reactor thermoneutral points. Dry autothermal reforming of methane was used as model example in this study. This study can be used for different autothermal processes to calculate the optimum conditions at which the process can be operated in heat integrated loop without the need of any external thermal energy.